N-[4-(3H-1,3,4-OXADIAZOLINE-2-THION-5-YL)PHENYL]-N'-SUBSTITUTED THIOUREAS - SYNTHESIS AND ANTIMICROBIOLOGICAL ACTIVITIES - (:unkn) unknown (VCH PUBLISHERS INC, 1991)
Diverse pharmacological properties are associated with 3H-1,3,4-oxadiazoline-2-thione derivatives. These include anticonvulsant1-4) and fungicidal5) properties. On the other hand thiourea derivatives possess antiphytoviral6), virucidal7), growth inhibitory8-10), and herbicide11) activities. All these data prompted us to combine these moieties into a single molecule. The compounds synthesized were tested for their antimicrobial activities against seven microorganisms.
Keywords: SUBSTITUTED THIOUREAS; INHIBITION